Incidence of cancer among firefighters - Mafra, Eriksen (Seven Editora, 2023)
Firefighters are exposed to carcinogens that can increase the risk of developing various types of cancer. Many systematic reviews and articles have already been produced around the world with few conflicting conclusions. The results of several studies and analyses in Brazil, the United States, Canada, and Australia will be addressed in this article. This overview of bibliographic reviews is intended to evaluate the consistency of conclusions among the systematic reviews available on the risk of cancer in firefighters. Literature research was conducted in several indexed databases and literature available on the Internet to retrieve studies aimed at evaluating the incidence of cancer and/or cancer mortality in firefighters. The results, among others, consistently reported a significant increase in the incidence of rectal, prostate, bladder, and testicular cancer as well as melanoma in firefighters compared to those in the general population. Results of reviews and studies suggest that various types of cancer may be more frequent in firefighters than in the general population. It is necessary to rethink models already proposed and active to institutionalize prevention programs, with the modernization of equipment and standardization of technologies, in addition to prophylactic measures that face the reduction of the development of cancer risk in professionals. After scenario analysis, preventive and mitigative measures will be sought to drastically reduce the incidence of the disease. DOI: 10.56238/pacfdnsv1-051